Mini-review: dietary influency and nutritional treatment in nephrolithiasis - Oliveira, M. C. [UNESP]; Goes, C. R. [UNESP] (Springer Nature, 2022)
Nephrolithiasis prevalence has increased worldwide in the last decades. Kidney stones formation has multifactorial pathogenic pathways, and obesity, dehydration, genetic influency, and metabolic diseases are considered risk factors. The dietary intake of calcium-rich foods, sodium, oxalate, citrate, uric acid, and protein, as well as fluids intake, are part of the dietary and nutritional aspects associated with stones prevention or promotion. The aim of this mini narrative review was to summarize the most recent evidence on dietary and nutritional factors involved in the treatment and control of kidney stones. Adequate fluid intake promotes increased urine output and prevents oversaturation of lithogenic products, such as oxalate, calcium, and urate. Artificially sweetened beverages and beer are not recommended, while citrus fruit juices, such as orange and lemon, teas, and coffee, are encouraged. Plant-based diet, low-fat, and calcium-rich dairy products, fruits, and vegetables may protect against stone formation by reducing sodium and purine intake, and increasing serum citrate and calcium intake. Meat, offal, and seafood are associated with increased hyperuricemia, a potential stone former due to urinary acidification. The diet prescription by the dietician should be made based on the evaluation of the patient’s usual dietary intake, metabolic profile, stone composition, preferences, and accessibility. Dietary patterns such as vegetarian diet, DASH diet, and Mediterranean diet are considered the best anti-lithogenic dietary patterns.
Keywords: Diet; Dietary patterns; Kidney stones; Nephrolithiasis; Nutrients